2012
DOI: 10.1177/1078155212442561
|View full text |Cite
|
Sign up to set email alerts
|

Hair repigmentation associated with the use of lenalidomide: Graying may not be an irreversible process!

Abstract: We report the first case of progressive hair repigmentation associated with the use of lenalidomide in an elderly patient with multiple myeloma. The influence of lenalidomide on follicular melanogenesis may involve removing the inhibitory influences of some cytokines such as IL-1, IL-6 and TNF-α. In addition, certain endocrine effects of lenalidomide on the hypophyseal-adrenal axis could explain its action on hair pigmentation. We further hypothesize that lenalidomide may be capable of stimulating migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Hair repigmentation of his beard and posterior scalp was noticed 6 weeks post-treatment, and pigmentation was maintained in these areas 3 months after the lenalidomide discontinuation (7). The authors of this report suggested that removing the inhibitory influences of inflammatory cytokines might influence follicular melanogenesis and that the hair greying process might not be irreversible (7). Additionally, other observations on the skin of stressed mice indicated that permanent graying resulted from the differentiation of melanocyte precursors by genotoxic influences rather than from the aging process or apoptosis of follicular melanocytes (8,9).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hair repigmentation of his beard and posterior scalp was noticed 6 weeks post-treatment, and pigmentation was maintained in these areas 3 months after the lenalidomide discontinuation (7). The authors of this report suggested that removing the inhibitory influences of inflammatory cytokines might influence follicular melanogenesis and that the hair greying process might not be irreversible (7). Additionally, other observations on the skin of stressed mice indicated that permanent graying resulted from the differentiation of melanocyte precursors by genotoxic influences rather than from the aging process or apoptosis of follicular melanocytes (8,9).…”
Section: Discussionmentioning
confidence: 97%
“…However, follicular melanogenesis and melanocyte viability are known to be unstable in the early stage of hair greying (6). A previous case reported an 81-year-old man with repigmentation of his depigmented hairs after treatment for multiple myelomas with lenalidomide, a 4-amino-glutamyl analogue of thalidomide (7). Hair repigmentation of his beard and posterior scalp was noticed 6 weeks post-treatment, and pigmentation was maintained in these areas 3 months after the lenalidomide discontinuation (7).…”
Section: Discussionmentioning
confidence: 99%
“…[72,73] Darkening of hair has also been reported as an incidental finding with other drugs such as defibrotide, cyclosporine, corticosteroid, etretinate, L-thyroxine, verapamil, tamoxifen, levodopa, cisplatin, acitretin, tri-iodothyronine, and lenalidomide. [71,[74][75][76][77] However, in most of these cases, drug-induced etiology of pigmentation could only be confirmed if hair had returned to its original color after drug withdrawal. The same could not be confirmed as most patients were continued on treatment with the suspected drug.…”
Section: Management Managementmentioning
confidence: 97%
“…Some authors conclude that immunotherapy can inhibit proinflammatory cytokines such as (TNF alpha and betha, IL1 and IL2) that could act as negative regulators of melanogenesis, explaining the repigmentation. 9,10 Other authors conclude that the melanocytes in the follicles could be activated by inflammation mediators such as cytokines or reactive oxygen species, explaining in many cases dermatological phenomena such as secondary folliculitis. 11 At the level of the follicle, there could be interactions between drugs directed to immunocheckpoint and ion channels of copper and zinc because some antigen structure could be shared.…”
Section: Discussionmentioning
confidence: 99%